Epidemiological trends of bronchial asthma symptoms in adolescent children in the Udmurt Republic. The results of long-term research - L. P. Matveeva; M. K. Ermakova; N. R. Kapustina (Аллергология и Иммунология в Педиатрии)
Annotation. Taking into account the spread of asthma symptoms in dynamics in different regions using proven techniques allows you to get the most complete picture of this process and identify regional features.Materials and methods. Monitoring of the spread of asthma symptoms was carried out within the confines of the ISAAC program from 2002 to 2019–2020. The results obtained were compared with the results of 1999. Udmurt teenagers aged 13–14, studying in schools of the republic, participated in the survey, a total of 12 856 people.Results. By 2019–2020, the prevalence of asthma symptoms increased compared to 1999 and was 10.2%. The problem of underdiagnosis of the disease persists. There is a decrease in severe forms of asthma and the frequency of recurrence of night and daytime symptoms. The number of children who responded to physical activity with difficulty breathing, as well as respondents with frequent attacks of non-infectious cough, increased significantly. In general, a negative trend is observed in the statistics of bronchial asthma symptoms.Conclusions. Long-term observation allowed us to obtain data that are an important contribution to understanding not only the trends of BA in the Udmurt Republic, but also in their further study.